Numidian clay deposits as raw material for ceramics tile manufacturing. (April 2020) - Moussi, B.; Hajjaji, W.; Hachani, M.; Hatira, N.; Labrincha, J.A.; Yans, J.; Jamoussi, F.
Abstract: We investigate the potential use in traditional ceramics of several clays collected in the Numidian Flysch Formation (Upper Oligocene) at Tabarka, and Sejnane; Northern part of Tunisia). The valorisation of these adopts the technique of dry process, which requires a mixture of powdered clay with 7% water. This allows rapid drying of uncooked tiles. The tiles are fired at four different temperatures (1000 °C, 1050 °C, 1100 °C and 1150 °C) in order to optimize technological parameters such as shrinkage, water absorption and flexural strength. The obtained tiles show acceptable drying and firing shrinkage (not exceeding 3%), and bending strength (between 13 and 16 N/mm 2 ) which are close to the required standards (EN ISO 10545–4, 15N/mm 2 for wall tiles). The absorption ranges from 10 to 20%, which classifies these products in group BIII according to the international standards (ISO 13006 and EN ISO 10545–3). Variation of shrinkage and water absorption with the firing temperature reveals that optimal range is 1125–1150 °C for the Tabarka samples, whereas the Sejnane products might be fired at lower values (~1025 °C). The Tabarka fired pieces exhibit strong brightness. These results suggest that these latter clays could be used for white products such as sanitary ware formulations while those from Sejnane ones are more appropriated for colored (red) applications. The X-ray diffraction on the fired tiles powders shows the formation of quartz which is initially present in the crude clays, and mullite that is present at all firing temperatures. Moreover, the presence of mullite due to the richness of Al2 O3 in Tabarka clays could support their refractory properties. Highlights: Potential use in traditional ceramics of Numidian Flysch was investigated. Obtained tiles show acceptable firing shrinkage 3% and bending strength at 16 N/mm 2 . Shrinkage and WA optimal range is 1150 °C for Tabarka and 1025°C for Sejnane samples. Fired tiles shows the formation mullite, especially in Tabarka clays richer in Al2 O3 . Abundant clayey geological raw material of Numidian can be used on ceramic industry.